Validation of Malay Mini Mental State Examination - Abidin, Zarina Zainan; Othman, Zahiruddin; Che, Wan AH (Malaysian Psychiatric Association, 2007)
Cognitive impairment cases referred to psychiatric clinic are very few especially those who have mild disease. Formal evaluation of cognitive impairment is time consuming and it involves consultation with an expert in psychological training. One clinically useful test for practitioners is the Mini Mental State Examination (MMSE). Although MMSE has shown good reliability and validity, using this instrument in a language and culture other than English may create problems. However the test has never been validated in Bahasa Malaysia even though it is a widely used screening test during patient’s clinical examination. This study was done to translate and validate MMSE into Bahasa Malaysia.